Revisiting the modifiable areal unit problem in the era of exposome-wide association studies: Assessing the performance of the CDC/ATSDR social vulnerability index at privacy-protecting spatial scales - Jonathan V. Lewis; Nathaniel MacNell; Ian D. Buller; Gary Larson; David C. Fargo; Charles P. Schmitt; Lawrence S. Kirschner; David M. Reif; Farida S. Akhtari; Cristina M. Justice; John S. House; Kyle P. Messier; et al. (Environmental Research, 2026)

Tree species richness and identity influence the abundance of excysted soil ciliates in young forest plantations - Eric Kanold; Robert W. Buchkowski; William C. Parker; Eric B. Searle; Christian Messier; Carlos Barreto (Pedobiologia, 2026)

Young temperate tree species show fine root trait acclimation to differences in water availability - Florentin C. Jaeger; Christian Messier; Friderike Beyer; Isabelle Aubin; William C. Parker; I. Tanya Handa (Plant and Soil, 2026)

Diversity in Resource Use Strategies Promotes Productivity in Young Planted Tree Species Mixtures - Joel Jensen; Haben Blondeel; Joannès Guillemot; Florian Schnabel; Hernán Serrano‐León; Harald Auge; Lander Baeten; Nadia Barsoum; Jürgen Bauhus; Christel Baum; Raimundo Bermudez; Friderike Beyer; et al. (Global Change Biology, 2025)
Mixed‐species forestry is a promising approach to enhance productivity, increase carbon sequestration, and mitigate climate change. Diverse forests, composed of species with varying structures and functional trait profiles, may have higher functional and structural diversity, which are attributes relevant to a number of mechanisms that can influence productivity. However, it remains unclear whether the context‐dependent roles of functional identity, functional diversity, and structural diversity can lead to a generalized understanding of tree diversity effects on stand productivity. To address these gaps, we analyzed growth data from 83,600 trees from 89 species across 21 young tree diversity experiments spanning five continents and three biomes. Results revealed a positive saturating relationship between tree species richness and stand productivity, with reduced variability in growth rates among more diverse stands. Structural equation modeling demonstrated that functional diversity mediated the positive effects of species richness on productivity. We additionally report a negative relationship between structural diversity and productivity, which decreased with increasing species richness. When partitioning net diversity effects, we found that selection effects played a dominant role in driving the overall increase in productivity in these predominantly young stands, contributing 77% of the net diversity effect. Selection effects increased with diversity in wood density. Furthermore, acquisitive species with lower wood density and higher leaf nitrogen content had higher productivity in more diverse stands, while conservative species showed neutral to slightly negative responses to species mixing. Together, these results suggest that combining acquisitive with conservative species allows acquisitive species to drive positive selection effects while conservative species tolerate competition. Thus, contrasting resource‐use strategies can enhance productivity to optimize mixed‐species forestry, with potential for both ecological and economic benefits.

Tree diversity shapes the spectral signature of light transmittance in developing forests - Laura J. Williams; Kyle R. Kovach; J. Antonio Guzmán Q.; Artur Stefanski; Raimundo Bermudez; Ethan E. Butler; Domitille Coq‐‐Etchegaray; Catherine Glenn‐Stone; Peter Hajek; Johanna Klama; Belinda E. Medlyn; Christian Messier; et al. (Ecology, 2025)
Greater tree diversity often increases forest productivity by increasing the fraction of light captured and the effectiveness of light use at the community scale. However, light may shape forest function not only as a source of energy or a cause of stress but also as a context cue: Plant photoreceptors can detect specific wavelengths of light, and plants use this information to assess their neighborhoods and adjust their patterns of growth and allocation. These cues have been well documented in laboratory studies, but little studied in diverse forests. Here, we examined how the spectral profile of light (350–2200 nm) transmitted through canopies differs among tree communities within three diversity experiments on two continents (200 plots each planted with one to 12 tree species, amounting to roughly 10,000 trees in total), laying the groundwork for expectations about how diversity in forests may shape light quality with consequences for forest function. We hypothesized—and found—that the species composition and diversity of tree canopies influenced transmittance in predictable ways. Canopy transmittance—in total and in spectral regions with known biological importance—principally declined with increasing leaf area per ground area (LAI) and, in turn, LAI was influenced by the species composition and diversity of communities. For a given LAI, broadleaved angiosperm canopies tended to transmit less light with lower red‐to‐far‐red ratios than canopies of needle‐leaved gymnosperms or angiosperm‐gymnosperm mixtures. Variation among communities in the transmittance of individual leaves had a minor effect on canopy transmittance in the visible portion of the spectrum but contributed beyond this range along with differences in foliage arrangement. Transmittance through mixed species canopies often deviated from expectations based on monocultures, and this was only partly explained by diversity effects on LAI, suggesting that diversity effects on transmittance also arose through shifts in the arrangement and optical properties of foliage. We posit that differences in the spectral profile of light transmitted through diverse canopies serve as a pathway by which tree diversity affects some forest ecosystem functions.

Young temperate tree species show different fine root acclimation capacity to growing season water availability - Florentin C. Jaeger; I. Tanya Handa; Alain Paquette; William C. Parker; Christian Messier (Plant and Soil, 2024)
Background and aims Changes in water availability during the growing season are becoming more frequent due to climate change. Our study aimed to compare the fine-root acclimation capacity (plasticity) of six temperate tree species aged six years and exposed to high or low growing season soil water availability over five years. Methods Root samples were collected from the five upper strata of mineral soil to a total soil depth of 30 cm in monoculture plots of Acer saccharum Marsh., Betula papyrifera Marsh., Larix laricina K. Koch, Pinus strobus L., Picea glauca (Moench) Voss and Quercus rubra L. established at the International Diversity Experiment Network with Trees (IDENT) field experiment in Sault Ste. Marie, Ontario, Canada. Four replicates of each monoculture were subjected to high or low water availability treatments. Results Absorptive fine root density increased by 67% for Larix laricina , and 90% for Picea glauca , under the high-water availability treatment at 0–5 cm soil depth. The two late successional, slower growing tree species, Acer saccharum and Picea glauca, showed higher plasticity in absorptive fine root biomass in the upper 5 cm of soil (PIv = 0.36 & 0.54 respectively), and lower plasticity in fine root depth over the entire 30 cm soil profile compared to the early successional, faster growing tree species Betula papyrifera and Larix laricina . Conclusion Temperate tree species show contrasting acclimation responses in absorptive fine root biomass and rooting depth to differences in water availability. Some of these responses vary with tree species successional status and seem to benefit both early and late successional tree species.

Enhancing Tree Performance Through Species Mixing: Review of a Quarter-Century of TreeDivNet Experiments Reveals Research Gaps and Practical Insights - Leen Depauw; Emiel De Lombaerde; Els Dhiedt; Haben Blondeel; Luis Abdala-Roberts; Harald Auge; Nadia Barsoum; Jürgen Bauhus; Chengjin Chu; Abebe Damtew; Nico Eisenhauer; Marina V. Fagundes; et al. (Current Forestry Reports, 2024)

A geospatial modeling approach to quantifying the risk of exposure to environmental chemical mixtures via a common molecular target - Kristin M. Eccles; Agnes L. Karmaus; Nicole C. Kleinstreuer; Fred Parham; Cynthia V. Rider; John F. Wambaugh; Kyle P. Messier (Science of The Total Environment, 2023)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

A global meta‐analysis of the relative extent of intraspecific trait variation in plant communities - Andrew Siefert; Cyrille Violle; Loïc Chalmandrier; Cécile H. Albert; Adrien Taudiere; Alex Fajardo; Lonnie W. Aarssen; Christopher Baraloto; Marcos B. Carlucci; Marcus V. Cianciaruso; Vinícius de L. Dantas; Francesco de Bello; et al. (Ecology Letters, 2015)
Recent studies have shown that accounting for intraspecific trait variation ( ITV ) may better address major questions in community ecology. However, a general picture of the relative extent of ITV compared to interspecific trait variation in plant communities is still missing. Here, we conducted a meta‐analysis of the relative extent of ITV within and among plant communities worldwide, using a data set encompassing 629 communities (plots) and 36 functional traits. Overall, ITV accounted for 25% of the total trait variation within communities and 32% of the total trait variation among communities on average. The relative extent of ITV tended to be greater for whole‐plant (e.g. plant height) vs. organ‐level traits and for leaf chemical (e.g. leaf N and P concentration) vs. leaf morphological (e.g. leaf area and thickness) traits. The relative amount of ITV decreased with increasing species richness and spatial extent, but did not vary with plant growth form or climate. These results highlight global patterns in the relative importance of ITV in plant communities, providing practical guidelines for when researchers should include ITV in trait‐based community and ecosystem studies.

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Threat-sensitive generalization of predator recognition by larval amphibians - Maud C. O. Ferrari; Grant E. Brown; François Messier; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2009)

Threat-sensitive learning of predators by larval mosquitoes Culex restuans - Maud C. O. Ferrari; François Messier; Douglas P. Chivers (Behavioral Ecology and Sociobiology, 2008)

Spatial and temporal distribution of chloroplast DNA polymorphism in a tropical tree species - H. Caron; S. Dumas; G. Marque; C. Messier; E. Bandou; R. J. Petit; A. Kremer (Molecular Ecology, 2000)
The level and the spatial organization of chloroplast DNA polymorphism were investigated in Dicorynia guianensis Hamshoff (Caesalpiniaceae) at different spatial and temporal scales. D. guianensis is a canopy tree of the rain forest that is distributed throughout the Guiana plateau in small aggregates. Twelve different haplotypes were identified using restriction analysis of polymerase chain reaction (PCR) amplified fragments of the chloroplast genome. When populations from different areas of French Guiana were compared, a clear geographical pattern of haplotype frequencies was identified along the Atlantic coast. This pattern is most likely the result of the restriction–expansion dynamics of the tropical forest during the Quaternary. At the local level, D. guianensis was characterized by a high level of within population diversity. Maintenance of within population diversity results from the dynamics of the aggregates; stochastic demography associated with the turnover of aggregates generates genetic differentiation among them. At the stand level, a strong spatial aggregation of haplotypes persisted from the adult to the seedling cohort indicating limited seed flow. There was also a strong difference in levels of diversity between the cohorts which suggested that recruitment over several years is needed in order to maintain genetic diversity during regeneration.

Genetic structure of the world’s polar bear populations - D. Paetkau; S. C. Amstrup; E. W. Born; W. Calvert; A. E. Derocher; G. W. Garner; F. Messier; I. Stirling; M. K. Taylor; Ø. Wiig; C. Strobeck (Molecular Ecology, 1999)
We studied genetic structure in polar bear ( Ursus maritimus ) populations by typing a sample of 473 individuals spanning the species distribution at 16 highly variable microsatellite loci. No genetic discontinuities were found that would be consistent with evolutionarily significant periods of isolation between groups. Direct comparison of movement data and genetic data from the Canadian Arctic revealed a highly significant correlation. Genetic data generally supported existing population (management unit) designations, although there were two cases where genetic data failed to differentiate between pairs of populations previously resolved by movement data. A sharp contrast was found between the minimal genetic structure observed among populations surrounding the polar basin and the presence of several marked genetic discontinuities in the Canadian Arctic. The discontinuities in the Canadian Arctic caused the appearance of four genetic clusters of polar bear populations. These clusters vary in total estimated population size from 100 to over 10 000, and the smallest may merit a relatively conservative management strategy in consideration of its apparent isolation. We suggest that the observed pattern of genetic discontinuities has developed in response to differences in the seasonal distribution and pattern of sea ice habitat and the effects of these differences on the distribution and abundance of seals.